Tri-Relasi Kompetensi sebagai “brand image” Pendidikan Nasional - Winarto Eka Wahyudi (Kuttab : Jurnal Ilmu Pendidikan Islam, 2018)
Education runs very dynamically. Because they have to adjust to the pulse of changing times so rapidly, at least three urgent challenges must be answered by national education. The problem of advancing information technology, nationalism and socio-cultural spirit is a sexy issue that must not only be discussed but must also be answered thoroughly. In certain aspects, if education only responds to the progress of science and science, it will give birth to mechanical humans who are far from spiritual and cultural values. For this reason, in the millennial era, it is necessary to form a "brand image" of national education by initiating three competencies that must be carried out in an integrated manner with one another: namely digital competence, national competence and cultural competence. Mainstreaming the three components in the millennial era is crucial, because of the challenges ahead, plurality empties through the three segments. Thus, providing understanding and competence of the nation's generation through these three things, in addition to being a capital to face the swift waves of changing times, also in the context of building a genuine national education self-image amid world education contestation